Novel ion exchange resin-based combination drug-delivery system for treatment of gastro esophageal reflux diseases - Mangesh Ramesh Bhalekar; Nitin Madhukar Kadam; Nilam Hindurao Patil; Nitin Somnath Gawale; Ashwini Madgulkar (Universidade de São Paulo, 2010)
The present study involves preparation and characterization of a combination tablet of ranitidine in immediate release form and domperidone in sustained release form, using ion exchange resins. Ranitidine lowers acid secretion, while domperidone release over a prolonged period improves gastric motility thus justifying this combination in gastro esophageal reflux diseases (GERD) and ensuring patient compliance. Drug loading was carried out by batch method & resinates were characterized using FTIR, XRPD. Resinates were formulated as a combination tablet and evaluated for tablet properties & in vitro drug release. Resinates provided sustained release of domperidone and immediate release of ranitidine. IR and X-ray studies indicate complexation of drug and resin along with monomolecular distribution of drugs in amorphous form in the resin matrix. The tablets of resinate combination showed good tablet properties. In-vitro drug release gave desired release profiles and ex-vivo drug absorption studies carried out by placing everted rat intestine in dissolution medium indicated statistically significant similarity in absorption from test and marketed formulation. The novelty of this study is that the retardation in release of domperidone from resinates is achieved by presence of weak resin in the formulation. O presente estudo envolve a preparação e a caracterização de associação do comprimido de ranitidina de liberação imediata e domperidona de liberação prolongada, utilizando resinas de troca iônica. A ranitidina diminui a secreção ácida, enquanto a liberação prolongada de domperidona melhora a motilidade gástica, justificando, dessa forma, a associação em doenças de refluxo gastroesofágico (DRGE) e garantindo a adesão do paciente. A carga de fármaco foi efetuada pelo método em batelada e os resinatos, caracterizados utilizando-se FTIR e XRPD. Os resinatos foram formulados como comprimido da associação e avaliados com relação às propriedades dos comprimidos e liberação do fármaco in vitro. Os resinatos proporcionaram a liberação prolongada da domperidona e a liberação imediata da ranitidina. IV e estudos de difração de raios X indicaram a complexação do fármaco e da resina junto com a distribuição monomolecular dos fármacos, em estado amorfo, na matriz da resina. Os comprimidos da associação do resinato apresentaram boas propriedades. Obtiveram-se os perfis de liberação in vitro e os estudos de absorção dos fármacos ex vivo realizados com intestino de rato em meio de dissolução indicaram semelhança significativa na absorção entre as formulações teste e comercializada. A inovação do trabalho é que o retardamento da liberação da domperidona dos resinatos é atingido pela presença de resina fraca na formulação.